Fukushima Daiichi fuel debris retrieval: results of aerosol characterization during laser cutting of non-radioactive corium simulants. Issue 1 (2nd January 2021) - Porcheron, Emmanuel; Dazon, Claire; Gelain, Thomas; Chagnot, Christophe; Doyen, Ioana; Journeau, Christophe; Excoffier, Emmanuel; Roulet, Damien
ABSTRACT: The production and dispersion of contaminated aerosols during the laser cutting of corium can potentially provide useful insights into the dispersion of contamination during the evacuation of damaged reactors during decommissioning. Quantitative assessments of contamination dispersion are fundamental to the development of a safety case for the decommissioning of the Fukushima Daiichi plant. This collaborative work between IRSN, ONET Technologies and CEA, managed by the Mitsubishi Research Institute on behalf of the Japanese Ministry of Economy, Trade and Industry, presents the characterization of aerosols generated during laser cutting of corium simulants both in air and under water. The objective is to obtain quantitative data for risk assessment related to the contamination released and disseminated when implementing this technique, over the next few years, in the process of decommissioning the damaged reactors. This paper presents a part of the results stemming from this project, focused on the characterization of aerosols produced during laser cutting of two representative corium simulants in air and underwater conditions. The experimental configuration also enabled investigation of the production of other material residues such as particle dross and water purity on the particulate composition of the aerosols. Ultimately, the radioisotope concentration distribution in the aerosols are transposed to radioactivity in order to assess the risk to radiation workers during decommissioning.